Conversion factors for residential wood energy in the European Union: an introduction to harmonizing units of measurement. (March 2021) - Glasenapp, S.; Fonseca, M.; Weimar, H.; Döring, P.; Aguilar, F.X.
Abstract: Wood energy data are reported in forest products and energy statistics but current use of heterogeneous units can result in major inconsistencies. Harmonization of wood energy statistics can benefit data quality and improve measuring sustainable practices, better informing policy-makers and analyzing feedstock competition. Harmonization of wood energy data and subsequent application in the forest product and energy sectors require appropriate conversion factors. We provide conversion factors for forest energy products relative to weight and volume for the residential sectors of EU28 member states. Selected forest products include wood from primary, secondary and tertiary sources considering differences in properties affecting conversion factors. Proposed conversion factors were derived from information on moisture content, heating value, density and changes in wood volumes due to swelling and shrinkage of wood. Heating values relative to weight denote conversion factors to transform weight to energy units that ranged from 13.88 to 17.14 MJ/kg. Computation of heating values relative to volume ranged from 7316 to 11, 053 MJ/m³. The use of extreme conversion factors in a sensitivity assessment showed that the ranges between minimum and maximum values accounted for as much as 27% of total wood energy consumption. Application of conversion factors to EU28 residential wood energy consumption revealed inconsistencies between forest products and energy statistics. Closer collaboration between experts and use of universal conversion factors at national levels will likely improve data quality and direct comparability. Conversion factors used in the residential sector can facilitate harmonization in non-residential sectors, but sector-specific product characteristics require further adjustment. Highlights: Conversion factors relative to weight range from 13.88 to 17.14 MJ/kg in EU28. Conversion factors relative to volume range from 7316 to 11, 053 MJ/m³ in EU28. Density, moisture content, change in volume and lower heating value affect factors. Use of extreme conversion factors span 27% of total wood energy consumption. Inconsistent residential consumption between forest products and energy statistics.